Anomalous self-reduction of layered double hydroxide (LDH): from α-Ni(OH)2 to hexagonal close packing (HCP) Ni/NiO by annealing without a reductant. Issue 6 (31st October 2014) - Ge, X.; Gu, C. D.; Wang, X. L.; Tu, J. P.
Abstract : An anomalous self-reduction phenomenon can occur for Ni LDH synthesized from an ionic liquid system. Abstract : The traditional concept that nickel layered double hydroxide (Ni LDH, also known as α-Ni(OH)2 ) converts to NiO after annealing has been taken without doubt and utilized to fabricate NiO for years. This work reports that an anomalous self-reduction phenomenon can occur for Ni LDH synthesized from an ionic liquid system.